Assessment of Accessibility for People with Disabilities to BRT Trans Mamminasata in Makassar City - Helmy, Ahnaf Riyandirga Ariyansyah Putra; Aska, Aulya Milatul (Universitas Negeri Makassar, 2023)
Trans Mamminasata BRT service delivery in the city of Makassar is still not able to provide a good service for people with disabilities. This can be seen in the existing condition of the existing BRT shelter. Therefore, this study aimed to evaluate the accessibility available on Trans Mamminasata BRT services to persons with disabilities. The research method used in this research is descriptive qualitative research method that aims to avoid the important details that are neglected due to quantitative methods are often the details are generalized into numbers and causing the existing information becomes neglected. Based on observations that have been made, found many irregularities in Mamminasata Trans Cosmos BRT service standards established in Indonesia. Some of the most common problems are the discrepancy of the size of the stop device against the prevailing standards, the unavailability of the special room for wheelchair users, the poor pedestrian conditions around the BRT shelter, the lack of available service information, and the presence of the eliminated bus facility. Based on this, it can be concluded that the condition of BRT stop Trans Mamminasata still not friendly to persons with disabilities in the city of Makassar.